From national monitoring to transnational indicators: reporting and processing of aquatic biology data under the European Environment Agency’s State of the Environment data flow - Moe, S. Jannicke; Mentzel, Sophie; Welch, Samuel A.; Lyche Solheim, Anne (Frontiers in Environmental Science, 2023)
Biological monitoring data from aquatic ecosystems are collected from 25 European countries on a yearly basis by the European Environment Agency (EEA) through the Water Information System for Europe (WISE). The purpose of the WISE-SoE data flows is to provide comparable indicators of pressures, states and impacts of surface waters and groundwaters on a pan-European scale. The dataflow labelled WISE-2 was established to obtain a harmonized flow of biology data reported as Ecological Quality Ratios (EQRs) from all surface water categories; rivers, lakes, transitional and coastal waters. The voluntary yearly WISE-2 biology data reporting is a supplement to the mandatory 6-yearly reporting of ecological status of water bodies according to the Water Framework Directive. Biology data are reported for the following biological quality elements (BQEs): phytoplankton, phytobenthos, macrophytes, macroalgae, angiosperms, benthic invertebrates and fish in rivers, lakes, transitional and/or coastal waters. The national EQR values represent a measure of the deviation from reference conditions for each biological quality element. The national EQR values are subsequently converted to normalized EQR values which are comparable across countries and enable pan-European assessments.